OP35 A national framework for anticipation in health care: the swiss proposal. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Eychmueller, S; Felber, S; Krones, T
Abstract : Background: Anticipatory planning including advance care planning has become one of the megatrends in health care. As in many countries, terminology and understanding of anticipatory planning varies significantly. Aim: For a common understanding of anticipation and guidance in clinical practice, we aimed to develop a national framework for anticipation in health care in Switzerland. Method: we undertook a national consensus project with representatives from all cultural regions in Switzerland. After review of the literature and existing guidelines and/or recommendations we performed a three Delphi process including additional national expert review. Results: We propose a three level model of anticipatory planning in health care. Level one aims to initiate general anticipatory planning including discussion on individual values, preferences and expectations; experts from various professional background (e.g. pastoral care, social care, psychology) may offer support on this level. Level two focuses on disease specific anticipatory care planning; expertise in regard of potential complication of specific diagnosis/disease trajectory is necessary to provide assistance while planning. Level three finally is dedicated to advance care planning (ACP) for clinical situations without capacity for judgement; guidance by professionals with a background in intensive and emergency care may be needed. Conclusions: a national consensus process on definitions of various levels for a participatory approach in anticipatory planning helps to create a solid basis for common understanding of anticipation in health care, to highlight professional roles and expertise for counselling on each level, and to prevent low quality in written documentation.